The Role of Strategic Vigilance as an Entrance to Achieving the Strategic Leadership in Saudi Universities - Bani Hani, Sylvia Ismail Mohammad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal the strategic vigilance’s impact in Saudi universities through its dimensions: (competitive vigilance, technological vigilance). The descriptive analytical approach was used in this research, and the study sample included (62) faculty members in three universities (Hail University, Umm Al-Qura University, Taibah University). The necessary analytical statistics were conducted, in addition to testing the validity of the hypotheses. It was concluded that there is an essential role for strategic vigilance as an entry point to achieve strategic leadership in Saudi universities. The results of hypothesis testing also showed that there is a significant positive impact at the significance level (0.05) of competitive vigilance and technological vigilance dimensions on strategic leadership. Accordingly, the study recommended adopting the requirements of strategic vigilance and employing them in Saudi universities.